PjBL-ESD as an innovation in science learning: Cultivating local wisdom values and students' critical thinking skills - Vilmala, Berry Kurnia; Kisworo, Banu; Rihan, Hanifa Ghina; Syafriani, Santhy (Education and Development Research, 2025)
Sustainability-oriented science education is important to improve critical thinking skills and instill local wisdom values. This study explores the implementation of Project-Based Learning based on Education for Sustainable Development (PjBL-ESD) as an innovation in science learning. This study uses a mixed method with an embedded design. Data were obtained through critical thinking tests, local wisdom value questionnaires, observations, and interviews, then analyzed using N-Gain. The results showed that students who studied with PjBL-ESD experienced a significant increase in critical thinking skills (N-Gain 0.67) in the moderate category. In addition, students better understood and appreciated local wisdom related to environmental conservation through science-based projects and traditional ecological knowledge (N gain 0.25). In conclusion, PjBL-ESD is an effective learning innovation that improves critical thinking skills and strengthens local wisdom values. This approach is recommended to support sustainability education in higher education.